Environmental Socialization and Paper Waste Creation Practice for Students of SMP Negeri 16 Surabaya: Kegiatan Sosialisasi Lingkungan Hidup dan Praktik Kreasi Limbah Kertas Bagi Siswa di SMP Negeri 16 Surabaya - Pandu Rudy Widyatama; Qurrotul Uyun; Annisa Nurul Jannah; Alvionita Wahyu Dinda Lestari; Patrisia Karmenita Ngene (Journal of Humanities Research Sustainability, 2024)
At SMP Negeri 16 Surabaya, a service learning (SL) project tackled the issue of paper waste by engaging 25 Adiwiyata team students in environmental socialization and creative practices, supported by the Surabaya City Environmental Agency and guided by PPG students from the State University of Surabaya. The project involved stages such as problem identification, planning, and service implementation, culminating in the creation of a 3-dimensional map of Indonesia from paper waste. This hands-on approach allowed students to apply theoretical knowledge while developing social skills and responsibility. The activity was successful, with enthusiastic student participation and the production of an impactful creative product. Background. In schools, paper waste is a worrying problem. Every day, paper is used for purposes, from student assignments, duplication of materials, to school administration. This accumulation of paper use is not balanced with an effective waste management system, so that a lot of waste paper is wasted without being reused. This condition not only contributes to the accumulation of waste in schools, but also negatively impacts the environment at large. Purpose. This activity is carried out with a service learning (SL) approach that integrates student learning experiences with services to the community. Through service learning (SL), students not only apply the theoretical knowledge gained in lectures, but also develop social skills, empathy, and responsibility. In this activity, students are directly involved in projects that are beneficial to the community, one of which is environmental socialization and paper waste creation practices for students (adiwiyata team) at SMP Negeri 16 Surabaya. Method. This activity is carried out through stages in the service learning (SL) approach, including problem identification and planning, classroom preparation and learning, service implementation, reflection, demonstration and evaluation, and sustainable development. Results. This activity was attended by 25 students of SMP Negeri 16 Surabaya with socialization activities supported by the Surabaya City Environmental Agency and creative practices guided by PPG students from the State University of Surabaya. This activity produces a creation product from paper waste in the form of a 3-dimensional map of islands in Indonesia. Conclusion. The activities carried out have been carried out well by showing students who are enthusiastic in participating in the activity, shown by the students who attended in accordance with the planned invitation and producing creative products.